A review and future of RPL dosimetry. (November 2022) - Yanagida, Takayuki; Okada, Go; Kato, Takumi; Nakauchi, Daisuke; Kawaguchi, Noriaki
Abstract: Radiophotoluminescence (RPL) is one luminescence phenomenon in which a new luminescent center is generated in a material by interaction with ionizing radiation. The luminescence center, so-called RPL center, can be observed by a conventional photoluminescence technique, and the luminescence intensity is proportional to the number of RPL centers, which is proportional to the radiation energy deposited and accumulated in the material. Therefore, RPL can be used for radiation dosimetry. Since discovery of RPL in the middle of the 20th century to the present, it has found successful industrial application in personnel dosimetry and is still one of the most reliable and actively used dosimetry techniques. This paper clarifies the fundamental RPL properties to be considered for radiation measurements and reviews the applications and recently reported RPL materials. Highlights: In RPL phenomenon, interaction with ionizing radiation forms a new luminescent center. Fundamental RPL properties for radiation dosimetry are discussed. Conventional applications of RPL are discussed. New materials and knowledge of RPL will advance the RPL technologies.